Peran Manajemen Keuangan Untuk Menambah Pendapatan di Canting Buana Kreatif Padang Panjang, Sumatera Barat - Sahroni Sahroni; Masno Marjohan; Sri Retnaning Sampurnaningsih (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
The purpose of this community service activity is for participants to understand how to manage finances effectively and efficiently, especially after the pandemic. In this training, it is hoped that participants will gain knowledge on how to allocate company funds or capital to finance business line needs, ensuring that the company's budget is distributed to the right posts and used for various purposes that benefit the company. After this activity, it is expected that participants will be able to plan their finances effectively and efficiently. The target of this activity is the manager of Canting Batik Crafts in Padang Panjang, West Sumatra. The implementation method consists of three stages. The first stage is preparation, including a pre-survey, team formation, proposal preparation and submission, coordination between teams and partners, as well as preparation of training tools and materials. The second stage is the program implementation stage in the form of socialization through counseling (material presentation) and discussions. The third stage is the evaluation and reporting stage. The evaluation is conducted by comparing the conditions of partners before and after the program implementation using interview and observation methods. Afterward, a report is prepared for further socialization.